2000
DOI: 10.1177/026119290002800107
|View full text |Cite
|
Sign up to set email alerts
|

Testing Wound-healing Activity in T15 Fibroblast Cultures: A Morphometric Analysis

Abstract: The purpose was to evaluate the use of mouse T15 fibroblast cell cultures for the investigation of wound-healing activity. In order to investigate their mechanisms of action, the effects of drugs with wound-healing activities were compared by using morphometric analyses by microscopy after cell staining. A number of parameters were used to evaluate the effects of titrated extracts from Centella asiatica and dexpanthenol (drugs that have been used in medical practice for their wound-healing activities) on cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 28 publications
2
18
0
1
Order By: Relevance
“…Fibroblast cell cultures have been proposed as a method for testing wound‐healing activity in vitro (Graham et al ., 1984). However, this approach has been used only in a few studies on the development of new drugs and for the investigation of the mechanism of action (Maquart et al ., 1990; Korkmaz et al ., 2000; Öztürk et al ., 2006; 2007). In this study, it was observed that TECA mainly increases mitotic activity (Table 2) and the number of polygonal cells (Table 3), and slightly stimulates collagen production in the NIH3T3 cells (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast cell cultures have been proposed as a method for testing wound‐healing activity in vitro (Graham et al ., 1984). However, this approach has been used only in a few studies on the development of new drugs and for the investigation of the mechanism of action (Maquart et al ., 1990; Korkmaz et al ., 2000; Öztürk et al ., 2006; 2007). In this study, it was observed that TECA mainly increases mitotic activity (Table 2) and the number of polygonal cells (Table 3), and slightly stimulates collagen production in the NIH3T3 cells (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblast cell cultures have been proposed as a method for testing wound-healing activity in vitro (Graham et al, 1984). However, this approach has been used in only a few studies on the development of new drugs and for the investigation of mechanism of action (Maquart et al, 1990;Korkmaz et al, 2000;. The data obtained with dexpanthenol and TECA clearly demonstrate that cell culture of chicken embryonic fibroblasts is a suitable model for the investigation of wound-healing activity, since these compounds cause specific morphological changes in the cultured fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…The methods for chicken embryonic fibroblast culture and for administration of DMSO, TECA, dexpanthenol and Hypericum extract into culture media were quite similar to that described earlier for the culture of T15 fibroblast cell lines (Korkmaz et al, 2000). The concentrations for TECA (5 and 10 g/mL) and dexpanthenol (1 and 10 g/mL) were selected on the basis of literature data (Lacroix et al, 1988;Maquart et al, 1990;Korkmaz et al, 2000), whereas the effective concentrations of Hypericum perforatum extract (1, 5, 10 and 100 g/mL) were determined after scanning a wide concentration range in pilot experiments. Dexpanthenol, TECA and Hypericum extract were dissolved in DMSO and the same dose of DMSO at 2 L/mL was used for control and experimental groups were compared to both DMSO and blank controls.…”
Section: Cell Culturementioning
confidence: 97%
See 2 more Smart Citations